1997
DOI: 10.2486/indhealth.35.285
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Lipid Peroxidation in the Liver of Mice Exposed to Magnetic Fields.

Abstract: To elucidate the biological effect of static magnetic fields (SMF), we measured lipid peroxidation in the liver, kidneys, heart, lungs and brain of mice exposed to SMF and also evaluated the combined effect of SMF exposure on the hepatotoxicity induced by treatment with carbon tetrachloride (CC14). Lipid peroxidation in the liver was significantly increased by exposure to 4.7 T of SMF for 3, 6, 24, or 48 h, whereas that in the kidneys, heart, lungs and brain was not changed compared to the control. The combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Several other studies have shown that exposure to EMFs increased free radical formation in various tissues (Moustafa et al 2001;Zmyslony et al 2004;Simko et al 2006). This study is consistent with the previous reports, showing that EMF caused lipid peroxidation in rat liver (Watanabe et al 1997) and that EMF increased malondialdehyde formation in the rat liver and brain (Romodanova et al 1990). The present study also revealed that plasma and brain GSH levels were decreased in EMF-exposed rats, which might indicate a reduction in antioxidant defence.…”
Section: Discussionsupporting
confidence: 94%
“…Several other studies have shown that exposure to EMFs increased free radical formation in various tissues (Moustafa et al 2001;Zmyslony et al 2004;Simko et al 2006). This study is consistent with the previous reports, showing that EMF caused lipid peroxidation in rat liver (Watanabe et al 1997) and that EMF increased malondialdehyde formation in the rat liver and brain (Romodanova et al 1990). The present study also revealed that plasma and brain GSH levels were decreased in EMF-exposed rats, which might indicate a reduction in antioxidant defence.…”
Section: Discussionsupporting
confidence: 94%
“…We also previously reported the suppression or enhancement of the genotoxic effects in microbial systems, cultured cells and animals, the suppression of food and water consumption and body weight in mice, and the enhancement of metallothionein content and lipid peroxidation in mice, with exposure to strong static EMFs (0.15-to 11.75-T) alone or co-exposure to static EMFs and chemicals (38)(39)(40)(41)(42)(43). Our previous studies suggested that the effects induced by strong static EMFs may be enhanced or suppressed by the stress reaction or cell cycle change.…”
Section: Discussionmentioning
confidence: 94%
“…In the group exposed to EMF for 18 months in that study, irregularity was observed in sinusoidal lumen diameters, the cell cytoplasm was empty and replaced by granules, chromatin was less condensed, and the space between the interior and exterior nuclear membrane expanded (29). Another study referred to EMF altering mitochondrial structures, particularly in hepatocytes (30).…”
Section: Discussionmentioning
confidence: 99%
“…MDA and SOD levels have been reported to increase and GSH to decrease in rats exposed to EMF at a frequency of 945 MHz and with a SAR value of 11.3 mW/ kg (31). High-frequency 4.7-T EMF has been shown to lead to LPO in mice by increasing TBARS (30).…”
Section: Discussionmentioning
confidence: 99%